Novel approach to discriminate left bundle branch block from nonspecific intraventricular conduction delay using pacing-induced functional left bundle branch block - Scholz, Eberhard P.; Fischer, Patrick; Lugenbiel, Patrick; Xynogalos, Panagiotis; Schweizer, Patrick Alexander; Scherer, Daniel; Thomas, Dierk; Katus, Hugo; Zitron, Edgar (Journal of interventional cardiac electrophysiology, 2018)
Left bundle branch block (LBBB) has a predictive value for response to cardiac resynchronization therapy as reported by Zareba et al. (Circulation 123(10):1061-1072, 2011). However, based on ECG criteria, the discrimination between complete LBBB and nonspecific intraventricular conduction delay is challenging. We tested the hypothesis that discrimination can be performed using standard electrophysiological catheters and a simple stimulation protocol.
Gesehen am 22.04.2020